The effect of complex falls prevention interventions on falls in residential aged care settings: A systematic review protocol - Francis-Coad, J.; Etherton-Beer, C.; Nobre, D.; Naseri, Chiara; Hill, Anne-Marie (University of Adelaide * Faculty of Health Sciences, 2017)
Review question/objective: The objective of this review is to synthesize the best available evidence on the effectiveness of complex falls prevention interventions on fall reductions in the residential aged care population, implemented at two or more of the following levels: organization, facility or resident. Specifically the review question is: What is the effect of complex falls prevention interventions on falls in residential aged care settings?